Long‐term white matter tract reorganization following prolonged febrile seizures. (23rd March 2017) - Pujar, Suresh S.; Seunarine, Kiran K.; Martinos, Marina M.; Neville, Brian G. R.; Scott, Rod C.; Chin, Richard F. M.; Clark, Chris A.
Summary: Objective: Diffusion magnetic resonance imaging (MRI) studies have demonstrated acute white matter changes following prolonged febrile seizures (PFS), but their longer‐term evolution is unknown. We investigated a population‐based cohort to determine white matter diffusion properties 8 years after PFS. Methods: We used diffusion tensor imaging (DTI) and applied Tract‐Based Spatial Statistics for voxel‐wise comparison of white matter microstructure between 26 children with PFS and 27 age‐matched healthy controls. Age, gender, handedness, and hippocampal volumes were entered as covariates for voxel‐wise analysis. Results: Mean duration between the episode of PFS and follow‐up was 8.2 years (range 6.7–9.6). All children were neurologically normal, and had normal conventional neuroimaging. On voxel‐wise analysis, compared to controls, the PFS group had (1) increased fractional anisotropy in early maturing central white matter tracts, (2) increased mean and axial diffusivity in several peripheral white matter tracts and late‐maturing central white matter tracts, and (3) increased radial diffusivity in peripheral white matter tracts. None of the tracts had reduced fractional anisotropy or diffusivity indices in the PFS group. Significance: In this homogeneous, population‐based sample, we found increased fractional anisotropy in early maturing central white matter tracts and increased mean and axial diffusivity with/without increased radial diffusivity in several late‐maturing peripheral white matter tracts 8 years post‐PFS. We propose disruption in white matter maturation secondary to seizure‐induced axonal injury, with subsequent neuroplasticity and microstructural reorganization as a plausible explanation.